Aging with board games: fostering well-being in the older population - Guardabassi, Veronica; Manoni, Evelyn; Di Massimo, Marta; Cirilli, Elisa; Maranesi, Alessandro; Nicolini, Paola (Frontiers in Psychology, 2024)
Introduction The increase in the average age of the population has resulted in a greater focus on interventions designed to facilitate successful Ageing. Notwithstanding its potential, the strategy of the board game remains relatively underexplored. This study aims to ascertain its role in fostering older people’s well-being. Specifically, it was hypothesized that the level of well-being associated with the gaming experience is greater than overall well-being, particularly when the level of difficulty is low. Methods From an initial number of 164 participants, a total of 132 older people made up the final sample (Mage = 74.05; SD = 5.62). They were divided into groups of four or five individuals and engaged in a gaming session of varying levels of difficulty: low (N = 44), medium(N = 49) and high (N = 36). Prior to each game session, participants completed a questionnaire regarding their general well-being. After the game session, they filled out a similar questionnaire regarding their well-being while gaming. Results The results showed that the level of well-being experienced while playing was significantly higher than that observed in daily life, F(1,131) = 14.604, p = 0.000, η2 = 0.100, particularly with board games with a low or medium level of difficulty, [F(2,126) = = 10.982, p = .001, η2 = 0.148]. Discussion Board games with an appropriate level of difficulty can be useful tools for promoting wellbeing in the older population. Future studies and possible interventions for people in the third and fourth ages will be discussed.